FROM WORK ENVIRONMENT TO EMPLOYEE LOYALTY: THE MEDIATING ROLE OF JOB SATISFACTION - Rina Masruroh; Disman Disman; Riska Riska (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2026)
This study examines the mediating role of job satisfaction in the relationship between the work environment and employee loyalty at a savings and loan cooperative in Kuningan Regency (referred to as KSP X) facing declining employee loyalty reflected in fluctuating and relatively high turnover. Grounded in Social Exchange Theory and Herzberg's Two-Factor Theory, the research adopts a quantitative associative design using a survey method. A saturated sampling technique was applied to the entire population of the cooperative's employees, and data were collected through a questionnaire and analysed using path analysis and the Sobel test. The findings reveal that the work environment has a positive and significant effect on job satisfaction and on employee loyalty, that job satisfaction has a positive and significant effect on employee loyalty, and that job satisfaction significantly mediates the effect of the work environment on employee loyalty in a partial mediation pattern. These results confirm that a good work environment strengthens employee loyalty most effectively when it also raises job satisfaction. The cooperative is therefore encouraged to improve its work environment and to give priority to job satisfaction as the main way to build loyalty and reduce turnover.